Overlying strata movement law and rockburst prevention & control for fully mechanized top coal caving face in extra-thick coal seams - Hai Rong; Longyue He; Yadi Wang; Xiangzhi Wei; Shilong Wei; Suihan Yang; Jincheng Li; Linlin Chen (Scientific Reports)
Abstract To investigate the movement law of overlying strata in the fully mechanized top-coal caving face of extra-thick coal seams and further achieve the effective prevention and control of rock burst. Taking the 12,240 working face of Gengcun Coal Mine as the engineering background, initially, the calculation formula for the collaborative deformation load of hard rock strata and the formula for the instability scale of hard rock strata are employed to precisely ascertain the position and instability scale of the key strata. Subsequently, a UDEC calculation model is established to comprehensively investigate the instability characteristics of the overlying hard rock strata. Simultaneously, a meticulous analysis of the working resistance of the on-site supports is carried out to validate the theoretical computations. Eventually, in light of the research findings, a rational determination of the cutting scale is made so as to offer a scientific foundation and efficacious guidance for the execution of roof pre-splitting blasting operations. The research results show that within 50 m above the 12,240 working face, there is one low-position hard strata and three medium-position hard strata. Under the influence of mining, the displacement field of the overlying hard strata is symmetrically distributed with respect to the central axis of the goaf. The stress rise areas on both sides of the goaf present a “hyperbolic” distribution, and the stress of the goaf roof and floor is released, showing an “elliptical parabolic belt” distribution. The periodic instability occurred about 8 m after the initial instability of the low-level hard rock layer, and the periodic instability occurred about 20 m after the initial instability of the middle hard rock layer 1. The goaf of the 12,220 working face in the north of the working face is a crucial reason for the support resistance of the upper part of the 12,240 working face being greater than that of the middle part and the middle part being greater than that of the lower part. When the working face advances 20–30 m, a distinct pressure accumulation area emerges in the middle of the working face and is regularly distributed as the working face advances. The monitoring results indicate that microseismic events are concentrated in the basic roof and medium-position strata 1, and energy events of 103 J are prone to occur. The basic roof and medium-position strata 1 are the key points for rock burst prevention of the working face. A roof cutting scale of no more than 10 m for the low-position hard strata can effectively reduce the rock burst risk. The research results provide theoretical support for roof pre-splitting and rock burst prevention of the 12,240 working face in Gengcun Coal Mine and can offer guidance for the prediction and prevention and control of rock burst risk in mines and working faces under similar conditions.